2020
DOI: 10.2147/cia.s249137
|View full text |Cite
|
Sign up to set email alerts
|

<p>Main Risk Factors Related to Activities of Daily Living in Non-Dialysis Patients with Chronic Kidney Disease Stage 3–5: A Case–Control Study</p>

Abstract: Introduction: Elderly people are at increased risk of falls, disability and death due to reduced functional reserve, decline in multiple systems functions, which affects their activities of daily living (ADL) and eventually develop into frailty. The ADL assessment is conducive to early detection to avoid further serious situations. Previous studies on patients' activities of daily living with chronic kidney disease (CKD) are mainly focused on dialysis patients. Little information is available on non-dialysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(62 reference statements)
0
9
1
Order By: Relevance
“…Consistent with our results, many studies have shown that CCI is associated with ADLs and functionality. [ 44 46 ] In contrast to our result, a study in older patients from Singapore reported that CCI was not associated with LOS, which was more than 21 days. [ 30 ] However, since LOS longer than 21 days is quite a long time for general geriatric practice, this result cannot be mentioned to reflect daily geriatric practice.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with our results, many studies have shown that CCI is associated with ADLs and functionality. [ 44 46 ] In contrast to our result, a study in older patients from Singapore reported that CCI was not associated with LOS, which was more than 21 days. [ 30 ] However, since LOS longer than 21 days is quite a long time for general geriatric practice, this result cannot be mentioned to reflect daily geriatric practice.…”
Section: Discussioncontrasting
confidence: 99%
“…People with severe functional limitations often experience particular difficulties with daily activities, which place a burden on the healthcare system [14][15][16]. Therefore, before making a healthcare plan, it was essential to identify predictive factors that were significantly related to functional limitations in the performance of basic and complex activities of daily living (ADLs and IADLs) [4,9,10]. This study developed a model to verify the relationships between demographic and health parameters and functional limitations in daily living, defined as ADL/IADL disability levels, among older adults in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Those proportions among older adults in southeastern Poland were 17% and 36%, respectively [7], they were 16.6% and 40.9% in India [6], and were 5.6% and 12.0% in Korea, respectively [8]. Such functional decline was a strong predictor of institutionalization, which leads to an increase in medical costs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The CCI is the most commonly used measure to assess comorbidity and is also commonly used in patients with conservative CKD and dialysis patients [ 34 , 35 , 36 ]. In dialysis patients, CCI is a strong predictor of mortality, and in older patients with conservative CKD, a higher comorbidity index is associated with functional decline [ 21 , 37 ]. Comorbidities are associated with the severity of depression, anxiety, and fatigue, which reduce the amount of physical activity in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Independent variables were analyzed using two models. In Model 1, we entered items of clinical significance from among variables that showed significant differences ( p < 0.001) between the two groups, referring to previous studies [ 1 , 19 , 20 , 21 ]. In doing so, items that could be intermediate variables for causality (length of hospitalization, FIM-walking score at hospitalization, number of rehabilitations) were excluded.…”
Section: Methodsmentioning
confidence: 99%